Propuesta para el diseño de un sistema de gestión de calidad (SGS), basado en la norma ISO 9001: 2008, en la empresa industrial papelera Ecuatoriana S.A., cantón Babahoyo, provincia de los Ríos, año 2014 - Méndez Tacuri, Andreina Paola (2015)
Total quality, represents the new horizon of business competitiveness, to integrate the joint effort of the organization involved in strategic planning and dedication to service both managers and employees; related to a shared strategic philosophy that focuses on continuous improvement to optimize the contribution margin and operating profit of the financial year. For which requires cultivating positive organizational behavior, enhancing the absorptive capacity of knowledge on the principles of quality, in order to achieve organizational development, based on collective learning. The company has established quality assurance of their products based on industrial automation, with the use of computer and electromechanical systems that manage and control circuit of machinery and industrial processes. However, it suffers from administrative problems with delays and operational and productive mismatches, which aims to improve through the management system ISO 9001. The investigation analyze, evaluate and diagnose organizational performance to be framed in meeting quality standards, in order to improve the quality of product-service, minimizing costs and maximizing profits. 100% of respondents said they did not know the 8 principles of quality, although most said the 61% that have indicators of quality management related to production processes, which in turn are closely linked to job performance of staff plant. Company focuses collective performance assessment, in product quality and process management available automated machinery